PROFITABILITAS, SOLVABILITAS, KEBIJAKAN DIVIDEN DAN PENGARUHNYA TERHADAP HARGA SAHAM SEKTOR PERINDUSTRIAN (IDXINDUST) IDX-IC - Helena Olivia Yosih Br. Nainggolan, (2022)
This research is quantitative with the aim of knowing profitability, solvency, dividend policy and its effect on stock prices in the Industrial sector (IDXINDUST) IDX-IC. In the Industrial sector (IDXINDUST) IDX-IC, there are fluctuations in the value of profitability, solvency, dividend policy and stock prices. The sampling technique used is slovin with an error margin of 5%. Based on the calculation of the slovin technique, a sample of 47 out of 54 companies registered in the Industrial Sector (IDXINDUST) IDX-IC was obtained. The hypothesis test in this study used the T test. The data in this study included panel data so as to find out the panel data regression and the T test used Eviews 10. Profitability in this study was measured using Net Profit Margin (NPM). Solvency in this study was measured using the Debt to Asset Ratio (DAR). Dividend policy in this study was measured using the Dividend Payout Ratio (DPR). Based on the results of this study, it can be seen that (1) Profitability has a positive effect on stock prices (2) Solvency has no effect on stock prices (3) Dividend policy has a positive effect on stock prices. Keywords: Profitability, Solvency, Dividend Policy and Stock Price.